To what is a transition into employment associated with an exit from poverty? - Taryn Ann Galloway (University of Oslo, Department of Economics, 2004)
A link between lack of employment and poverty is often made implicitly, but can rarely be enumerated in any sort of satisfactory manner. We would therefore like to ask the question: to what extent does acquiring employment increase a poor household's probability of exiting poverty? Register data from the entire resident population of Norway serves as the basis for the analysis. We distinguish between full-time and part-time employment and also include an investigation into the effect transfers have on the probability of exiting poverty,with or without a concurrent change in employment status. Norway with its generous social welfare system and well-functioning labor markets provides a unique opportunity to abstract to a certain extent from many complicating factors in investigating these questions.
Keywords: I32; J20; 330; Unemployment; Employment; Poverty; Beschäftigung; Armut; Norwegen